Visual Studio 2012 and .NET 4.5 expert development cookbook : over 40 recipes for successfully mixing the powerful capabilities of .NET 4.5 and Visual Studio 2012 - Sur, Abhishek (Quick answers to common problems., 2013)
This book is written in a cookbook-style format and provides practical, immediately usable task-based recipes that provide solutions to common development problems and help you adapt to the latest .NET technologies. This book is aimed at Visual Studio 2012 and .Net developers who want to gain advanced understanding and sharpen their existing skillsets and adapt to new .NET technologies. Basic understanding of .NET and C# is assumed. The purpose of this book is to give under the hood expertise in .NET and help you to face common problems on latest technologies.